1989
DOI: 10.1021/bi00448a007
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional proton and phosphorus-31 NMR spectra and restrained molecular dynamics structure of an extrahelical adenosine tridecamer oligodeoxyribonucleotide duplex

Abstract: Assignment of the 1H and 31P NMR spectra of an extrahelical adenosine tridecamer oligodeoxyribonucleotide duplex, d(CGCAGAATTCGCG)2, has been made by two-dimensional 1H-1H and heteronuclear 31P-1H correlated spectroscopy. The downfield 31P resonance previously noted by Patel et al. (1982) has been assigned by both 17O labeling of the phosphate as well as a pure absorption phase constant-time heteronuclear 31P-1H correlated spectrum and has been associated with the phosphate on the 3' side of the extrahelical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 59 publications
3
53
0
Order By: Relevance
“…While X-ray crystallography has provided much of our understanding of these DNA structural variations, increasingly, high-resolution NMR (particularly 'H/IH NOESY) has also begun to provide detailed three-dimensional structural information on duplex oligonucleotides (Broido et al, 1984;Feigon et al, 1983;Frechet et al, 1983;Hare et al, 1983;Kearns, 1984;Scheek et al, 1984;Schroeder et al, 1986Schroeder et al, , 1987van de Ven & Hilbers, 1988). Importantly, NMR experiments have suggested that the duplex conformation in solution (Assa-Munt & Kearns, 1984;Clore et al, 1985;Gorenstein et al, 1988;Nikonowicz et al, 1989;Patel et al, 1987;Rinkel et al, 1987) may not be identical with the static picture provided by X-ray diffraction in the crystal state. This has raised the question whether some of the sequence-specific structural variations observed in the X-ray crystallographic studies are the result of less profound crystal packing forces.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…While X-ray crystallography has provided much of our understanding of these DNA structural variations, increasingly, high-resolution NMR (particularly 'H/IH NOESY) has also begun to provide detailed three-dimensional structural information on duplex oligonucleotides (Broido et al, 1984;Feigon et al, 1983;Frechet et al, 1983;Hare et al, 1983;Kearns, 1984;Scheek et al, 1984;Schroeder et al, 1986Schroeder et al, , 1987van de Ven & Hilbers, 1988). Importantly, NMR experiments have suggested that the duplex conformation in solution (Assa-Munt & Kearns, 1984;Clore et al, 1985;Gorenstein et al, 1988;Nikonowicz et al, 1989;Patel et al, 1987;Rinkel et al, 1987) may not be identical with the static picture provided by X-ray diffraction in the crystal state. This has raised the question whether some of the sequence-specific structural variations observed in the X-ray crystallographic studies are the result of less profound crystal packing forces.…”
mentioning
confidence: 96%
“…Recently we have attempted to utilize 31P N M R to define sequence-specific variations in the backbone conformation of oligonucleotides Nikonowicz et al, 1989;Schroeder et al, 1989). Variations of 31P chemical shifts of individual phosphates in duplex oligonucleotides have been suggested to be attributable to torsional angle changes in the deoxyribose phosphate backbone.…”
mentioning
confidence: 99%
“…Twodimensional (2D) NMR, in particular 2D NOE spectra, when used in conjunction with energy-refinement calculations, can be used to determine the high-resolution structure of DNA fragments where subtle changes in structure can be detected (Zhou et al, 1987;Nilges et al, 1987;Nikonowicz et al, 1989;Pieters et al, 1990). A major obstacle to accurately depicting a structure using this methodology is the problem of extracting a large number of accurate interproton distances from the 2D NOE cross-peak intensities.…”
mentioning
confidence: 99%
“…In general there is a slight decrease in the R factor during the refinement cycles (decreasing from approximately 0.4 to 0.3). We believe our %RMSvol factor better represents the quality of the NMR refinement than the R factor (3,20,28,62). The latter heavily weighs the large NOESY volumes.…”
Section: Figure 8 Continuedmentioning
confidence: 99%
“…A "crankshaft" motion interconverts BI and BII conformations with only a modest movement of the phosphate. It is largely this variation in ε and ζ (as well as 8,3,36,39,62,68) that allows the sugar phosphate backbone to "stretch" or "contract" to allow for variations in the local structure of B-DNA.…”
Section: P Chemical Shifts and Jh3′-p Coupling Constantsmentioning
confidence: 99%